Identification and validation of plasma proteome signatures associated with MRI measurements in healthy individuals. (31st December 2021) - Shi, Liu; Hillary, Robert Francis; Marioni, Riccardo E.; Campbell, Archie; Hayward, Caroline; Stolicyn, Aleks; Whalley, Heather C.; Buckley, Noel; Nevado‐Holgado, Alejo J
Abstract: Background: Peripheral biomarkers reflecting early neurodegeneration change are critical to the development of treatments for Alzheimer's disease (AD). The most widely used indicator of AD neurodegeneration in life at present is neuroimaging evidence of brain atrophy. We therefore performed a proteomic analysis of plasma to derive biomarkers associated with neuroimaging in prodromal disease stage. Method: To identify blood‐based proteins relating to neurodegeneration ("N") in preclinical or prodromal disease stage, we used SOMAscan assay to measure 5033 proteins in two groups of healthy individuals (discovery group = 564, validation group = 497) selected from Generation Scotland cohort. We firstly performed both linear regression and protein co‐expression network to identify differentially expressed proteins and co‐expressed protein modules associated with "N" in the discovery group. We then validated such associations in the validation group. Result: Using linear regression, we identified different proteins that were significantly associated with whole brain volume, cortical volume and hippocampus volume after multiple correction, indicating that the associations between proteins and "N" were dependent on brain regions. From protein co‐expression network analysis, we identified seven modules (from 20 to 2088 proteins) in the discovery group, all of which were significantly preserved in the validation group. Furthermore, several modules were significantly associated with "N" and such associations were affected by sex and APOE genotype. Moreover, we replicated the associations between differentially expressed proteins and modules with "N" in the validation group. Conclusion: Our study is the largest we are aware of to report a plasma biomarker indicative of neurodegeneration in prodromal disease stage both in terms of the number of proteins assayed and in sample size. We identified and validated a groups of proteins in two large independent groups of healthy individuals. These proteins provide tractable targets for further mechanistic studies of neurodegeneration pathology, particularly in preclinical stages of Alzheimer's.